Measuring the Impact of Microplastics in the Citarum River on Women's Reproductive Health: A Chronic Exposure Biomarker Study in the Community - Erika Herliana; Sanny Edinov; Septi Viantri Kurdaningsih; Mahfuzhah Deswita Puteri (CV. Get Press Indonesia, 2025)
Riverine populations that rely on contaminated water bodies for everyday activities and food sources are most affected by the growing environmental and public health concern of microplastic pollution in river ecosystems. One of the world's most polluted rivers, the Citarum River is a high-risk environment for long-term exposure to microplastics, which may have an impact on women's reproductive health. An analytical cross-sectional design with an environmental and biomonitoring approach was applied to women of reproductive age (18–45 years) who had resided in the study area for at least two years, representing chronic exposure conditions. Environmental samples of river water, sediment, and locally consumed fish were analyzed using micro-FTIR or Raman spectroscopy, with polymer confirmation by Py-GC-MS. Individual exposure was assessed through fecal microplastic counts and urinary measurement of plastic-related chemical biomarkers, including phthalate metabolites (MEHP) and bisphenol A (BPA). The results demonstrated elevated levels of microplastics in environmental matrices and biological samples. Higher exposure categories were consistently associated with increased oxidative stress and inflammatory biomarkers, reduced anti-Müllerian hormone levels, elevated gonadotropins, and a higher prevalence of menstrual cycle disturbances. These findings indicate a dose–response pattern linking chronic microplastic exposure with biological stress and reproductive dysfunction. Overall, this study provides empirical evidence that long-term exposure to microplastics in contaminated river environments may pose a significant risk to women’s reproductive health, underscoring the need for environmental control and targeted public health interventions.